Workforce Diversity and It’S Benefits In Organizations: Exploring the Conflict Between Rationalism and Faith through Workforce Diversity in Organizations (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Golding uses the flashbacktechnique of Pincher Martin moreextensively in his next novel, FreeFall (1959). Unlike his first three novels, Free Fall is told with a first person narrator, an artistnamed Samuel Mountjoy. The novel takes as a model Dante's La Vita Nuova, a collection of lovepoems interspersed with Dante's own commentary on the poems. Golding uses thecharacter Mountjoy to comment on the conflict between rationalism and faith.